Experimental investigation on the bubble formation from needles with and without liquid co-flow. (20th July 2019) - Muilwijk, Corné; Van den Akker, Harry E.A.
Graphical abstract: Highlights: Bubbling rate measurements with a microphone as well as with a high-speed camera. A new correlation for bubble diameter for bubbling with and without co-flowing liquid. Correlations to identify surface tension, inertia controlled and period-2 bubbling. A novel pressure ratio to quantify constant flow and constant pressure condition. Abstract: We report experiments on bubble formation from needles with and without liquid co-flow, carried out with needles in the range of 0.79 < d n < 2.06  mm, for gas flow rates up to 4.5 cm 3 /s per needle, and with liquid co-flow velocities up to 0.4 m/s. Bubble sizes and frequencies were obtained by means measuring an acoustic signal in the pressurized chamber upstream, which is validated by high-speed imaging analysis. Bubble contours, bubble growth curves and time return plots were obtained to analyse the bubble formation process. Different bubbling regimes are distinguished and a novel dimensionless pressure ratio is proposed to forecast the emergence of weeping and the transition from constant flow rate bubbling to constant chamber pressure bubbling. A single correlation for the non-dimensional bubble size with and without liquid co-flow was developed and validated with the experimental data obtained in the present study.